Footloose and Pollution-Free - Ederington, Josh; Levinson, Arik; Minier, Jenny (The Review of Economics and Statistics, 2005)
In numerous studies, economists have found little empirical evidence that environmental regulations affect trade flows. In this paper, we propose and test several common explanations for why the effect of environmental regulations on trade may be difficult to detect. We demonstrate that whereas most trade occurs among industrialized economies, environmental regulations have stronger effects on trade between industrialized and developing economies. We find that for most industries, pollution abatement costs are a small component of total costs, and are unrelated to trade flows. In addition, we show that those industries with the largest pollution abatement costs also happen to be the least geographically mobile, or footloose. After accounting for these distinctions, we measure a significant effect of pollution abatement costs on imports from developing countries, and in pollution-intensive, footloose industries.